2009
DOI: 10.3758/pbr.16.4.671
|View full text |Cite
|
Sign up to set email alerts
|

The effect of frequency of shared features on judgments of semantic similarity

Abstract: Insight into the structure of conceptual knowledge can be gleaned by examining how statistical regularities in the semantic structure of concepts affect semantic processing. Two similarity judgment experiments revealed that pairs of concepts sharing relatively rare features were judged to be more similar than concepts sharing an equal number of relatively frequent features. Simulations confirmed that these results are consistent with a recurrent connectionist network model of semantic processing in which units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
(43 reference statements)
1
8
0
1
Order By: Relevance
“…They found faster response times to highly distinctive compared to shared features, and suggested that following the presentation of either a concept or a feature, highly distinctive features are activated faster than shared features. Mirman and Magnuson (2009) extended these findings with a concept-concept similarity rating task, in which concepts sharing a highly distinctive feature were judged as significantly more semantically similar than concepts sharing a highly frequent (i.e. shared) feature.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…They found faster response times to highly distinctive compared to shared features, and suggested that following the presentation of either a concept or a feature, highly distinctive features are activated faster than shared features. Mirman and Magnuson (2009) extended these findings with a concept-concept similarity rating task, in which concepts sharing a highly distinctive feature were judged as significantly more semantically similar than concepts sharing a highly frequent (i.e. shared) feature.…”
Section: Introductionmentioning
confidence: 73%
“…Specific types of brain damage are associated with impairments in processing distinctive compared to shared features (Alathari, Trinh Ngo, & Dopkins, 2004; Martin, 1992; Moss & Tyler, 1997; Tyler & Moss, 2001; Warrington, 1975). Building on these patient findings, some investigators have hypothesised that distinctive features have a special representational status which confers a facilitatory effect during conceptual processing in healthy individuals (Cree, McNorgan, & McRae, 2006; Hamilton & Geraci, 2006; Mirman & Magnuson, 2009). Cree et al (2006) tested this hypothesis in concept-feature and feature-concept verification tasks in which features were either highly distinctive or shared.…”
Section: Introductionmentioning
confidence: 99%
“…Comme rapporté ci-après, des études se sont attachées à déterminer le rôle joué par les traits sémantiques. Mirman et Magnuson (2009) ont ainsi montré que les traits sémantiques rares avaient un rôle privilégié dans le traitement de la signification. Un autre argument concernant l'importance des traits sémantiques provient d'étude utilisant le paradigme de l'amorçage.…”
Section: L'imageabilité Comme Variable Sémantiqueunclassified
“…Distinctive features are important to differentiate between closely related concepts, typically members of the same semantic category, as they occur in only one or a very few concepts. The crucial role played by distinctive features in semantic processing has been reported in several studies involving both healthy subjects (Marques 2005;Mirman and Magnuson 2009) and patients (Alathari et al 2004;Duarte et al 2009;Garrard et al 2005;Laisney et al 2011;Rogers et al 2004), as well as in connectionist models (Cree et al 2006;Rogers et al 2004;Mirman and Magnuson 2009;Moss and Tyler 2000). Not all the distinctive features, however, have the same salience for the representation of a concept (Cree et al 2006).…”
Section: Accounting For Salient and Marginal Distinctive Featuresmentioning
confidence: 92%